Data Governance Design for Optimization of Hospital Management Information System (SIM-RS) at ABC Regional Hospital - Muhammad Furqan Nazuli; Irfan Walhidayah; Neng Ayu Herawati; Lenny Putri Yulianti; Kridanto Surendro (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2025)
The increasing complexity of hospital data management requires a robust Data Governance (DG) framework to ensure data quality, security, and compliance. This study focuses on developing a DG framework tailored to the Hospital Management Information System (SIM-RS) at RSUD ABC to enhance data integration, accessibility, and regulatory adherence. A qualitative approach with a case study method was employed, involving interviews and document analysis to identify key challenges in data management. The proposed DG framework aligns with ICD-10 and regulatory requirements, ensuring interoperability and efficient data processing. Implementing the Master Patient Index (MPI) reduces duplicate records, while Two-Factor Authentication (2FA) and AES-256 encryption strengthen data security. FHIR standards facilitate seamless data exchange across healthcare systems, optimizingoperational efficiency. AI-driven data analytics further enhances clinical decision-making and administrative workflows. Evaluation of the framework demonstrates significant improvements in data quality, regulatory compliance, and risk management, leading to improved patient care and reduced medical errors. The High-Level Roadmap outlines a phased implementation strategy for sustainable DG adoption. Future research may explore performance metrics, Blockchain integration, and organizational change management to refine DG practices in healthcare institutions further.